PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PADA PT BCA Tbk (Fokus Ekonomi, 2011)
Company currently must begin to focus on delivering value (value) and increase customerloyalty. Loyalty means consumers returned again and again to conduct business transactions(purchases), although probably instead the company's product the best product on the market orhave the lowest prices. This